Praxeology Analysis of The Arabic Language Textbook for Madrasah Ibtidaiyah - Cindy Aqmarina Allail; Asep Sopian; Nalahuddin Saleh; Hikmah Maulani (Jurnal Internasional Pendidikan Bahasa Arab, 2025)
This study aims to analyze the Arabic language textbook for Grade 1 of Madrasah Ibtidaiyah, published by the Directorate of KSKK, Ministry of Religious Affairs of the Republic of Indonesia, and to identify the characteristics of Arabic language task design from the perspective of didactic anthropology theory, specifically praxeology. The research method employed in this study is descriptive qualitative, utilizing a literature research design. Data collection techniques include both primary and secondary sources. Primary sources consist of the Arabic language textbook for Grade 1 published by the Directorate of KSKK, while secondary sources encompass relevant books and journals. Data analysis employs qualitative methods, which include data collection, data reduction, data presentation, and conclusion drawing. The results indicate that the first part of the task design (T1) could not be analyzed using praxeology, as it did not incorporate specific techniques. Furthermore, the types of tasks (T2-T6) have not effectively constructed the theory of students' ability to communicate in Arabic, as the overall task presentations rely heavily on teacher direction. Additionally, obstacles to student learning were identified, including ontogenic and didactic challenges.